The Influence Of Relationship Marketing And E-Service Quality On Customer Loyalty Through Customer Satisfaction - Nila Kusumawati; Siti Asiyah; Muhammad Agus Salim (LP2M IAIN Palopo, 2026)
This study aims to analyze the effect of relationship marketing and e-service quality on customer loyalty through customer satisfaction among Shopee users in Malang City. The rapid development of e-commerce has increased competition among platforms, making customer loyalty an important factor for business sustainability. Therefore, companies need to understand the factors that influence customer loyalty. This research uses a quantitative approach with a survey method. Data were collected through online questionnaires distributed to 112 respondents using purposive sampling techniques. The analysis method used Partial Least Square (PLS) to test the relationship between variables. The results show that relationship marketing has a positive and significant effect on customer satisfaction, while e-service quality does not significantly affect customer satisfaction. Furthermore, e-service quality and customer satisfaction have a positive and significant effect on customer loyalty. However, relationship marketing does not directly affect customer loyalty. Customer satisfaction is proven to mediate the relationship between relationship marketing and customer loyalty, but it does not mediate the effect of e-service quality on customer loyalty. The findings indicate that customer satisfaction plays a crucial role in strengthening customer loyalty. Companies are advised to focus on improving relationship marketing strategies and enhancing customer experience to maintain long-term loyalty.